Different Grades of Body Mass Index is Correlated with Left Atrium and Ventricle Structure in Patients with Hypertensive Heart Disease (Indian Journal of Public Health Research & Development, 2020)
Background: Hypertensive Heart Disease (HHD) is usually followed by cardiac remodeling. Differentgrades of Body Mass Index (BMI) also influence the cardiac structure. Hence, we evaluate the cardiacstructure of HHD patients with various BMI grades.Materials and Method: This cross-sectional study involves 50 consecutive patients with HHD (hypertensiveheart disease) from the Cardiology and Vascular Medicine Departement, Soetomo General HospitalIndonesia. Echocardiographic examination was done using GE vivid 7. Statistics were evaluated with SPSS25.0.Results: The research showed that the grades of BMI (body mass index) was positively correlated withLA major (r=0.335), RA Major (r=0.371), LVD Mass (r=0.341), LVS Mass (r=0.303), LVPWD (r=0.369),LVPWS (r=0.391), and inversely correlated with LVSI Dopp (r=-0.376). Obese (BMI>30) patientshave significantly lower ejection fraction compared to normoweight (BMI
Keywords: Cardiac Structure, Echocardiography, Hypertension, Obese, Remodelling